Keberhasilan implementasi aplikasi sistem keuangan desa (Siskeudes) di kecamatan Pondok Kelapa Bengkulu Tengah - Abdullah; Asmi Khairani Putri Harahap (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2023)
This study aims to prove the influence of superior support, training and use of technology on the successful implementation of the Village Financial System (Siskeudes) application. The research was conducted at the Village Office of Pondok Kelapa District, Central Bengkulu Regency, Bengkulu Province. The population is all village apparatus. The research samples were village heads, village secretaries, financial officers, and siskeudes operators. Sampling criteria, researchers used purposive sampling method. This study uses a quantitative approach. Data was collected directly from the respondents using a questionnaire containing written statements with a Likert scale. Data analysis used SPSS version 22.0. The results of the study show that: superior support, training, and use of technology are proven to have a positive influence on the successful implementation of the siskeudes application. Support from superiors, training and the use of technology had a positive impact on village officials in encouraging the successful implementation of the Siskeudes application. The presence of technology makes the Village Office have a competitive advantage. The more qualified information technology is applied, the effectiveness/success of the resulting information system will be even higher. This research can contribute to providing theoretical support related to the Technology Acceptance Model (TAM) and the DeLone and McLean IS Success Model which suggest that superior support, training and use of technology have an influence on the successful implementation of village financial system applications (siskeudes).